Functionalized Magnetite Nanoparticles Using Two New Ionic Liquids for Efficient Oil Spill Cleanup - Noorah A. Faqihi; Mahmood M. S. Abdullah; Mohd Sajid Ali; Hamad A. Al‐Lohedan; Zainab M. Almarhoon (Journal of Chemistry)
Recently, magnetite nanoparticles (MNPs) have gained great attention for oil spill cleanup due to their unique properties, e.g., high oil removal efficiency, high surface area, and response to an external magnetic field. The efficiency of MNPs for oil spill uptake can be enhanced by functionalizing their surface using different materials. Furthermore, the functionalization of MNP surface using these materials promotes their chemical stability. This study aims to functionalize the surface of magnetite nanoparticles (MNPs) using two newly synthesized hydrophobic ionic liquids (ILs) and apply them for oil spill cleanup. ILs were synthesized by the reaction of glycidyl-4-nonyl ether (GE) with fatty amines, either octadecylamine (OA) or dodecylamine (DA), to yield the corresponding amines, GEOA and GEDA, respectively. GEOA and GEDA were quaternized with acetic acid (AA) to produce the corresponding ILs, GEOA-IL and GEDA-IL. The produced ILs, GEOA-IL and GEDA-IL, were applied for the surface modification of magnetite nanoparticles (MNPs), producing surface-modified MNPs, GO-MNPs and GD-MNPs, respectively. GO-MNPs and GD-MNPs were characterized using Fourier transform infrared, X-ray diffraction, transmission electron microscopy, dynamic light scattering, contact angle, and vibrating sample magnetometer. Their oil removal efficiency (ORE) was investigated at different MNP : crude oil ratios ranging from 1 : 1–1 : 50. GO-MNPs and GD-MNPs showed high ORE even at low MNP ratios. Furthermore, GO-MNPs showed higher oil removal efficiency than GD-MNPs, which may be explained using GEOA-IL containing a longer alkyl chain for MNP surface modification in comparison to GEDA-IL. Furthermore, GO-MNPs and GD-MNPs displayed excellent reusability in five cycles, with a slight decrease in ORE with increasing cycles.